Pelatihan Peningkatan Keterampilan Belajar Peserta Didik Menggunakan Aplikasi Canva di Sekolah Perbatasan Indonesia-Malaysia - Iwan Ramadhan; Imran Imran; Maria Ulfah; Stella Prancisca; Ahmad Yani T; Linda Linda; Uray Rosa Febrianti; Agung Wahyudi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service activity is to improve students' learning skills using the Canva application at SMA Negeri 1 Jagoi Babang, Bengkayang Regency (Indonesia – Malaysia Border School). The method of implementing this service uses training and assistance in making products. The evaluation instrument uses survey percentages and is analyzed descriptively. The results of this service show that training activities using the Canva application provide positive benefits and impacts for students, where students can understand the Canva application as an application that can support it in learning activities. Students are able to use this application and produce output in the form of design products, one of which is presentation material.